Factors affecting substance abuse treatment across different treatment phases - Flora, Katerina (International Journal of Psychosocial Rehabilitation, 2013)
The effective therapy of substance abuse is attributed to a wide range of factors. A relevant bibliography review has high- lighted those factors, which are most commonly employed by mental health professionals: Readiness (recognition, taking steps, ambivalence), Self-efficacy, Expectation about the therapy outcome, Satisfaction by the therapy treatment, Perceived Social Support, Depression/Anxiety/Stress levels of the client (clinical profile), Positive and Negative Emotions and the way in which clients realize the Meaning of Life. These factors have been thoroughly researched for the purposes of the current study during the different treatment stages of a residential treatment program. The sample included 157 clients. In total, four measurements of the factors have been conducted in the three basic stages of treatment (Counseling Centre, Res- idential Phase, Social Re-integration). The analysis of the Binary Logistic Regression Design revealed a statistically signi- ficant affect in factors, such as Meaning of Life (transition process from Counselling Centre to Residential Phase), Recog- nition and Sex (retention in the Residential Phase), Expectation, Stress and Satisfaction (completion of Residential Phase), Taking Steps, Satisfaction, Social Support and Depression (staying in Social Integration Phase) The findings of the study both confirm the important role already recognized factors play in treatment and present the impact new factors can have on the therapeutic outcome.